2021
DOI: 10.1007/s10646-021-02376-8
|View full text |Cite
|
Sign up to set email alerts
|

Synonymous single nucleotide polymorphism in arsenic (+3) methyltransferase of the Western mosquitofish (Gambusia affinis) and its gene expression among field populations

Abstract: Naturally occurring arsenic is toxic at extremely low concentrations, yet some species persist even in high arsenic environments. We wanted to test if these species show evidence of evolution associated with arsenic exposure. To do this, we compared allelic variation across 872 coding nucleotides of arsenic (+3) methyltransferase (as3mt) and whole fish as3mt gene expression from three field populations of Gambusia affinis, from water sources containing low (1.9 ppb), medium-low (3.3 ppb), and high (15.7 ppb) l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…There was a significant upregulation of the As3mt gene in the wound sites of both sexes in vivo. Arsenic methyltransferase (AS3MT) detoxifies inorganic arsenic in many species including humans [57], rodents [58], and fish [59,60]. The upregulation of the AS3MT gene in the skin of both male and female mice exposed to NaAsO 2 in this study demonstrated the ability of NaAsO 2 to affect the skin.…”
Section: Discussionmentioning
confidence: 64%
“…There was a significant upregulation of the As3mt gene in the wound sites of both sexes in vivo. Arsenic methyltransferase (AS3MT) detoxifies inorganic arsenic in many species including humans [57], rodents [58], and fish [59,60]. The upregulation of the AS3MT gene in the skin of both male and female mice exposed to NaAsO 2 in this study demonstrated the ability of NaAsO 2 to affect the skin.…”
Section: Discussionmentioning
confidence: 64%